2021
DOI: 10.1038/s41598-021-88135-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological projections in the upper reaches of the Yangtze River Basin from 2020 to 2050

Abstract: Understanding the impact of climate change on runoff is essential for effective water resource management and planning. In this study, the regional climate model (RCM) RegCM4.5 was used to dynamically downscale near-future climate projections from two global climate models to a 50-km horizontal resolution over the upper reaches of the Yangtze River (UYRB). Based on the bias-corrected climate projection results, the impacts of climate change on mid-twenty-first century precipitation and temperature in the UYRB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…It has been suggested that under the global warming scenario, land‐ocean temperature contrasts and the low‐level monsoon circulation will progressively strengthen and thus generate more precipitation (Bhowmick et al., 2021). Similar projections have been reported for the UYR (Gu et al., 2018; Huang et al., 2021); for example, Gu et al. (2018) suggested that the annual mean precipitation will increase by 3.62% under RCP4.5 (1.81°C) and 7.65% under RCP8.5 (2.26°C) over the Yangtze River basin, including the UYR.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been suggested that under the global warming scenario, land‐ocean temperature contrasts and the low‐level monsoon circulation will progressively strengthen and thus generate more precipitation (Bhowmick et al., 2021). Similar projections have been reported for the UYR (Gu et al., 2018; Huang et al., 2021); for example, Gu et al. (2018) suggested that the annual mean precipitation will increase by 3.62% under RCP4.5 (1.81°C) and 7.65% under RCP8.5 (2.26°C) over the Yangtze River basin, including the UYR.…”
Section: Discussionsupporting
confidence: 70%
“…The Yangtze River is the third largest river system in the world, accounts for nearly 40% of China's mean annual discharge, and supports the livelihoods of millions of people. The upper reaches of the Yangtze River (UYR) supply ∼46% of the multiyear average annual runoff and possess abundant water and hydropower resources (Huang et al., 2021). The large interannual and decadal variations in the monsoon precipitation leave the basin vulnerable to droughts and floods (S. L. Yang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial mean annual rainfall and air temperature variation across the UYRB is shown in Figure 3. The difference in rainfall between the northwest and southeast of the watershed seems to be considerable, as seen in Figure 3a, which is in accordance with the analysis of [62,67]. As reported by [62], the spatial distribution of precipitation over the UYRB is extremely heterogeneous, and in general, the rainfall decreases from the southeastern to the northwestern part of the basin.…”
Section: Preliminary Analysissupporting
confidence: 89%
“…The data used in this study include precipitation data sets from a RegCM4 simulation and observational data sets. The precipitation that has been simulated by RegCM4 for the period from 1989 to 2012 was based on the model configuration scheme from Huang et al [26]. In addition, the EAR-Interim reanalysis data were used as initial and boundary conditions to perform dynamic downscaling with a resolution of 50 km.…”
Section: Precipitation Datamentioning
confidence: 99%